2019
DOI: 10.1080/15384047.2019.1617570
|View full text |Cite
|
Sign up to set email alerts
|

Schedule-dependent potentiation of chemotherapy drugs by the hypoxia-activated prodrug SN30000

Abstract: Hypoxia-activated prodrugs (HAPs) are hypothesized to improve the therapeutic index of chemotherapy drugs that are ineffective against tumor cells in hypoxic microenvironments. SN30000 (CEN-209) is a benzotriazine di-N-oxide HAP that potentiates radiotherapy in preclinical models, but its combination with chemotherapy has not been explored. Here we apply multiple models (monolayers, multicellular spheroids and tumor xenografts) to identify promising SN30000/chemotherapy combinations (with chemotherapy drugs be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Patient tumour specimens can be contaminated by non-tumour cells which, when the specimens are grown as organoids, can outcompete the tumour cells and limit the effectiveness of the organoids at modelling human cancer [ 151 ]. Organoids have been reported to recapitulate hypoxic gradients [ 152 ]; however, their use for evaluating hypoxia-targeting drugs is challenging, since addition of the drug to the culture media causes physical disturbance that alters oxygen gradients in the media and will change the hypoxia status of the organoids [ 153 ]. Finally, a hallmark of cancer cells is anchorage-independent growth, yet, unlike spheroids or in vivo tumour models, tumour organoids are anchored to a basement membrane matrix.…”
Section: Patient-derived Models Of Hnsccmentioning
confidence: 99%
“…Patient tumour specimens can be contaminated by non-tumour cells which, when the specimens are grown as organoids, can outcompete the tumour cells and limit the effectiveness of the organoids at modelling human cancer [ 151 ]. Organoids have been reported to recapitulate hypoxic gradients [ 152 ]; however, their use for evaluating hypoxia-targeting drugs is challenging, since addition of the drug to the culture media causes physical disturbance that alters oxygen gradients in the media and will change the hypoxia status of the organoids [ 153 ]. Finally, a hallmark of cancer cells is anchorage-independent growth, yet, unlike spheroids or in vivo tumour models, tumour organoids are anchored to a basement membrane matrix.…”
Section: Patient-derived Models Of Hnsccmentioning
confidence: 99%
“…Studies highlight its heightened activity on tumor spheroids, leading to significant tumor growth delay when combined with radiation . In addition, SN30000, when used with gemcitabine, effectively inhibits the proliferation of reoxygenated tumor cells . The binding of EF5 may serve as a promising biomarker for hypoxia stratification and the assessment of SN30000 treatment response .…”
Section: Drugs Containing N-oxide Groupsmentioning
confidence: 99%
“… 135 In addition, SN30000, when used with gemcitabine, effectively inhibits the proliferation of reoxygenated tumor cells. 136 The binding of EF5 may serve as a promising biomarker for hypoxia stratification and the assessment of SN30000 treatment response. 137 It was found that the substitution pattern of the heterocyclic scaffold influences the back-oxidation of the intermediately formed radical anion (e.g., TPZ •– ) and thus the selective hypoxic release of hydroxyl radicals.…”
Section: Drugs Containing N -Oxide Groupsmentioning
confidence: 99%
“…( 188 ) proved that, compared with monolayer tumor cells, SN30000 has higher activity on tumor spheroids, and when combined with radiation, it can cause significant tumor spheroid growth delay. Moreover, when used together with or before gemcitabine, SN30000 can effectively inhibit the proliferation of reoxygenated tumor cells ( 189 ). EF5 binding may be a promising biomarker for hypoxia stratification and SN30000 treatment response assessment ( 190 , 191 ).…”
Section: Sn30000mentioning
confidence: 99%